(untitled) (Revista Latino-Americana de Enfermagem, 2005)
This study aimed to identify alterations in the intensity at which the negative behaviors of the victims of traumatic brain injury (TBI) affect the main family caregiver comparing the periods before and after the trauma and to verify the relation between the intensity of these alterations and time passed after the traumatic event. Participants were 50 caregivers of victims with different levels of dependence after TBI. The effect of the victim’s behaviors on the caregiver was measured by means of a Likert scale, in view of eleven negative behaviors cited in literature. According to the caregiver, the victim was more aggressive, anxious, dependent, depressed, irritated, and forgetful after the trauma, with a more explosive temperament, more self-centered, impulsive, with greater social inadequacy and mood oscillation. The first six cited behaviors were the ones that affected the caregiver more negatively. No relation was found between the passed time and the effect of the behavioral alterations